Functionally Isolated Sarcoplasmic Reticulum in Cardiomyocytes: Experimental and Mathematical Models - Diogo C. Soriano; Rosana A. Bassani; José W. M. Bassani (Bioengineering, 2025)
The interaction among the various Ca2+ transporters complicates the assessment of isolated systems in an intact cell. This article proposes the functionally isolated SR model (FISRM), a hybrid (experimental and mathematical) approach to study Ca2+ cycling between the cytosol and the sarcoplasmic reticulum (SR), the main source of Ca2+ for contraction in mammalian cardiomyocytes. In FISRM, the main transmembrane Ca2+ transport pathways are eliminated by using a Na+, Ca2+-free extracellular medium, and SR Ca2+ release is elicited by a train of brief caffeine pulses. Two compounds that exert opposite effects on the SR Ca2+ uptake were characterized by this approach in isolated rat ventricular cardiomyocytes. The experimental FISRM was simulated with a simple mathematical model of Ca2+ fluxes across the SR membrane, based on a previous model adapted to the present conditions. To a fair extent, the theoretical model could reproduce the experimental results, and confirm the main assumption of the experimental model: that the only relevant Ca2+ fluxes occur across the SR membrane. Thus, the FISRM seems to be a valuable framework to investigate the SR Ca2+ transport in intact cardiomyocytes under physiological and pathophysiological conditions, and to test therapeutic approaches targeting SR proteins.